SURVEI DAN PEMERIKSAAN GULA DARAH GUNA MENCEGAH TERJADINYA KOMPLIKASI AKIBAT DIABETES MELITUS PADA WARGA RT 06 RW 02 KELURAHAN SUKAJAYA KECAMATAN SUKARAMI PALEMBANG - Victoria Ire Tominik; Pra Dian (Jurnal Abdimas Musi Charitas, 2018)
Diabetes Mellitus is a degenerative disease that requires a proper and serious handling, as it can lead to chronic illness. Type 2 diabetes is the most common form of diabetes, accounting for 85% of diabetics. People with type 2 diabetes often occur from the age of 40. The number of cases of diabetes mellitus in Indonesia, ranked fourth in the world after India, China, and the United States. Although the number of diabetics in South Sumatra is not high enough, but the data from Health Office states, the number of DM patients from year to year tend to fluctuate in 2013 as many as 21,418 people, in 2014 decreased to 7,541 patients, but in 2015, increased again to 14,042 patients . This community service is done in the area of RT 06 RW 02, Suka Jaya Village, Kec. Sukarami, Palembang on January 14 - February 13, 2016. The number of people who come to check there are 41 people. The result of blood glucose examination when the residents of RT. 06 RT. 02 most normal blood sugar levels were 36 people (87.9%), hypoglycemia 3 people (7.3%) and hyperglycemia 1 person (2.4%).